DIFFERENCES IN SPEECH STRATEGIES OF MEN AND WOMEN IN ENGLISH: A SOCIOPRAGMATIC APPROACH - Daminjonova Risolat Muzaffar qizi; Sobirova Feruza Islomjon qizi (Bright Mind Publishing, 2025)
This article examines the differences in speech strategies used by men and women in English through a sociopragmatic lens. Although gender equality movements of recent decades have reduced many traditional linguistic distinctions, certain speech patterns remain deeply rooted in cultural norms. Drawing on the works of leading scholars such as Robin Lakoff, Deborah Tannen, Peter Trudgill, Jennifer Coates, and John Gray, the study explores lexical, pragmatic, and interactional features characteristic of gendered communication. Comparative insights from English and Uzbek further highlight how national culture, social expectations, and communicative traditions influence gender-based speech behavior. The analysis contributes to the broader understanding of gender sociopragmatics and the continual evolution of language within changing social contexts.
Keywords: Communicative, dominant, concept.